Scholia on vireos: a field guide to the family Vireonidae - Helzer, Aiden Grant, author; Beachy-Quick, Dan, advisor; Cooperman, Matthew, advisor; Thomas, Adam, committee member (Colorado State University. Libraries, 2024)
Using birds as image bearers, Scholia on Vireos: A Field Guide to the Family Vireonidae is a bird book of poems. The poems are foremost an experiment in the form and music of contemporary poetry. Each genus of the family has a particular form which was developed to represent it, and the syllable count of the lines was often inspired by the individual species's song. There is at least one poem for each species of bird. The poems also experiment with multiple languages (Ancient Greek, Latin, the Romance Languages, especially French and Italian) and with grammar and linguistics. Aside from the family of birds, the poems take inspiration from religion, philosophy, and mythology.
Keywords: mythology; poetry; theology; philosophy; birds; religion